Algoritmos heurísticos de otimização da proteção e manobra em redes de distribuição de energia - Comassetto, Lorenzo (2008)
The new regulations of the electricity sector have requested from the power utilities great performance efficiency on their distribution systems, requiring more rigorous quality and continuity energy levels. In Brazil, the privatization of the power utility companies has been allowing the adoption of new planning and operation policies, that necessarily consider the system reliability and its economic constraints. Regarding this the companies are looking for objectively estimate all the necessary system investments in order to achieve safe and economic continuity for its consumers. At planning level, there are several alternatives, such as complex systems of larger flexibility, new feeders allowing several possibilities of load transfer, isolating permanent faults confining outages to smaller sections of line, remote operated maneuver and protection equipment and supervised substations featuring devices to help fault location. However, these alternatives normally mean large sums of investment which results are not always easy to measure, due to the difficulty of identifying its benefits from those produced by other accomplished actions. At operational level, it is possible to achieve results on medium and short term through the efficient dimension of emergency dispatching crews, maneuver and maintenance plans, contingency studies, protection devices readjustment, strategic use of protection and maneuvers devices and so forth. The power utility companies have planning areas that define the best practices through its professionals' experiences associated to computing tools. Traditionally, these tools help the professionals with power flow and short circuit simulation, losses calculation, protection coordinating diagrams, etc. Some tools and methods capable to proceed reliability simulations through several criteria have been proposed recently. For example, through continuity indicators such as SAIDI and SAIFI, through network topology and equipment alternatives, as developed by Violin and Martinez [2004], through the number of customers or non-supplied energy helping the decision of inserting or removing equipment, as demonstrated by Abaide [2005], or even through reduction of interrupted customers number by the network reconfiguration due to contingency events as described by Bernardon [2007]. However during the studies of these alternatives many simplifications are usually assumed, mostly on the protection devices models. Due to that, they are considered as completely stable and it is just verified the overload operation possibility. The unsuitable protection devices interruptions caused by coordination problems are totally unconsidered. This thesis aims at presenting the algorithms developed to help determining the best distribution resources alternatives in order to increase the network reliability according to basic continuity criteria and the dynamic relationship among protection and maneuver devices. The developed computing tool can also automatically determine all the protection devices adjustments along the distribution network in order to achieve the best technical and economical application. To check the efficiency of the proposed methods, real case studies are presented with data from power utility companies.